Heart Rate Variability Characterization Using a Time-Frequency Based Instantaneous Frequency Estimation Technique - Malarvili, M.B.; Rankine, L.; Mesbah, M.; Colditz, P.B.; Boashash, B. (Springer, 2006)
In this paper, a new method for characterizing the newborn heart rate variability (HRV) is proposed. The central of the method is the newly proposed technique for instantaneous frequency (IF) estimation specifically designed for nonstationary multicomponent signals such as HRV. The new method attempts to characterize the newborn HRV using features extracted from the time–frequency (TF) domain of the signal. These features comprise the IF, the instantaneous bandwidth (IB)and instantaneous energy (IE) of the different TF components of the HRV. Applied to the HRV of both normal and seizure-suffering newborns, this method clearly reveals the locations of the spectral peaks and their time varying nature. The total energy of HRV components, ET and ratio of energy concentrated in the low-frequency (LF)to that in high-frequency (HF) components have been shown to be significant features in identifying the HRV of newborn with seizures.